Detection of BaP in seawater based on multi-walled carbon nanotubes composites immunosenor - Yan, Yirou; Qiu, Chengjun; Qu, Wei; Zhuang, Yuan; Chen, Kaixuan; Wang, Cong; Zhang, Ruoyu; Wang, Ping; Wu, Yuxuan; Gao, Jiaqi (Frontiers in Chemistry, 2022)
Benzo(a)pyrene, as the main polycyclic aromatic hydrocarbon pollutant in marine oil spill pollution, has negative effects on marine ecology and human health. A facile and sensitive method of rapid benzo(a)pyrene detection in seawater is essential for marine conservation. In this paper, a novel immunosensor was fabricated using a multi-walled carbon nanotubes-chitosan composite loaded with benzo(a)pyrene antibody. This immunosensor was based on a biosensing assay mechanism that used multi-walled carbon nanotubes-chitosan composites as conductive mediators to enhance electron transfer kinetics. Then, potassium ferricyanide was used as an electrochemical probe to produce an electrochemical signal for the voltammetric behavior investigation of the immune response by differential pulse voltammetry. Under optimal experimental conditions, the peak current change was inversely proportional to the benzo(a)pyrene concentration in the range of 0.5 ng·mL-1 and 80 ng·mL-1 with a detection limit of 0.27 ng·mL-1. The immunosensor was successfully applied to assay BaP in seawater, and the recovery was between 96.6 and 100%, which exhibited a novel, sensitive and interference-resistant analytical method for real-time water environment monitoring. The results demonstrate that the proposed immunosensor has a great potential for application in the monitoring of seawater.